Gonzalez, E., Stachowiak-Szymczak, K., & Amanatidou, D. (Eds.). (2023). Community Translation: Research and Practice. London: Routledge. https://doi.org/10.4324/9781003247333 (pp. 248) - Li, Huadong; Zhang, Jia (Linguistica Antverpiensia, New Series – Themes in Translation Studies, 2024)
/